Selecting the Most Reliable 14C Dating Material Inside Mortars: the Origin of the Padua Cathedral. Issue 2 (13th March 2019) - Addis, Anna; Secco, Michele; Marzaioli, Fabio; Artioli, Gilberto; Arnau, Alexandra Chavarría; Passariello, Isabella; Terrasi, Filippo; Brogiolo, Gian Pietro
ABSTRACT: In order to radiocarbon ( 14 C) date a building, several components of the mortar could be used, such as the mortar binder, the lime lumps, the charcoal particles and shell fragments eventually present among the aggregates. In particular, the mortar binder requires a purification treatment in order to separate it from other sources of carbon, which could change the 14 C signature of the binder invalidating the dating process. Here, we present the application of the Cryo2Sonic method to 14 C dating of the ancient building structures unearthed during excavation at the Padua Cathedral complex. The dated samples were pretreated by using Cryo2Sonic method and the improved Cryo2Sonic version 2.0, recently developed by introducing additional steps such as centrifugation of the mortar suspension and gravimetric sedimentation of the binder fractions. The Cryo2Sonic version 2.0 relies heavily on the characterization of the mortar and of the purified binder fractions, allowing the isolation of a reliable 14 C datable mortar fraction. Through this new method, the 14 C dating of different ancient structures excavated next to the Padua Cathedral allow to identify the first religious complex of the city of Padua (3rd–4th centuries AD).